Strategi Branding UMKM Spikoe Blonceng Legendaris di Kelurahan Rungkut Kidul Surabaya - Wilma Cordelia Izaak; Abd. Ghofar; M. Fabbian Rachmansyah; M. Arya Baharudin Amin (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Branding and Digital Marketing can be a new breakthrough for the problems that have been faced by small and medium scale business actors in marketing and introducing their products to potential consumers, especially umkm spikoe who are in the Rungkut Kidul sub-district, Surabaya. Umkm Spikoe actually has enormous potential because of the quality of the products and continuous innovation. However, the obstacle is the lack of knowledge related to branding and digital marketing strategies which hampers the development of these UMKM.These problems were known to researchers after conducting observations and interviews with business owners who gave rise to research and analysis methods related to the problems that have occurred so far. The solutions offered by researchers to business owners are logo and packaging improvements, assistance in creating accounts and social media content, assistance in creating and managing market accounts and offering insight regarding nano influencers and Instagram advertising.With the various alternative solutions we provide, it is hoped that Spikoe business owners will be able to compete and continue to be able to keep up with the times and technology that continues to develop rapidly